Peningkatan Kompetensi Pedagogis Guru melalui Pelatihan STEAM Terintegrasi Local Genius Magelang - Istiningsih, Galih; Dhuta Sukmarani; R Arri Widyanto; Puji Rahmawati (Universitas Nusantara PGRI Kediri, 2024)
This community service aims to improve the quality of the implementation of the Adiwiyata School at SDN Gelangan 3, Magelang City, especially in terms of the integration of environmental culture and local genius, so that the school can participate better in provincial level competitions. Community Service Method: The community service method used includes socialization, training, and STEAM practices integrated with Magelang's local genius. This approach aims to improve teachers' abilities in implementing an environmental-based curriculum and developing environmentally friendly facilities and infrastructure in schools. The results of this community service indicate that 70% of teacher participants are able to implement strategies, models, and learning techniques that actively involve students, 70% of teacher participants are able to develop local issues in the context of environmental education, and 70% of teacher participants have succeeded in compiling teaching modules containing environmental education. The conclusion of this community service has succeeded in increasing the capacity of teachers at SDN Gelangan 3 in implementing the Adiwiyata School, with better integration of environmental culture and local genius, although further efforts are still needed to achieve more optimal results at the provincial level.